Computer Assisted Learning Media and Decimal Board: How it Impact on Elementary Students’ Concept Mastery? - Rahmawati, Helmi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
The lack of students’ mastery of decimal fractions has become a current issue among researchers. The comparisin of decimal fraction values was still an obstacle for students. The use of learning media in this study is the Computer Assisted Learning Media and Decimal Board can be a solution to these problems. This study aimed to describe the increase of elementary studentsâ€™ concept mastery on decimal fractions subject matter. Descriptive-quantitative method with pre-test and post-test was carried out to achieve the research objectives. The subjects in this study were the 4th grade students (22 students) in the East Lombok area. The students’ concept mastery was measured using a multiple-choice test instrument of 10 items. The research data were analyzed descriptively and statistically using paired sample t-test. The results showed that students’ concept mastery increased after learning (pre-test: 54.5%; post-test: 77.27%). The results of statistical tests using the paired sample t-test also showed that students’ concept mastery had increased significantly after learning (p < 0.05). Based on the results of the study, it can be concluded that learning using Computer Assisted Learning Media and Decimal Boards can improve elementary school students’ concept mastery on decimal fractions subject matter.